A review: properties of silicon carbide materials in MEMS application - Marsi, Noraini; Majlis, Burhanuddin Yeop; Mohd Yasin, Faisal; Zainal Abidin, Hafzaliza Erny; Hamzah, Azrul Azlan (UNIMAP, 2020)
The paper presents the review properties of silicon carbide materials in the MEMS application. The study aims to explore silicon carbide in MEMS technology which considers the development of microscale and integrated devices that combine electronics, electrical and mechanical elements. MEMS has become a key area micro-device technology which incorporates materials, mechanical, electrical, chemical and optical disciplines as well as fluid engineering. The prevalence of MEMS technology in harsh environments has grown tremendously in recent years, especially at high temperatures up to 1240 ̊C, wider bandgap (2.3 – 3.4 eV), a higher breakdown field (30 × 105 V/cm), a higher thermal conductivity (3.2 – 4.9 W/cm- K), a higher saturation velocity (2.5 × 107 cm/s), higher oxidation, corrosive environments and higher radiation. Recent developments in robust MEMS for extreme environments such as MEMS pressure sensors have been widely used in ships, warships, gas turbine engines, cars and biomedical equipment. The growing demand for MEMS pressure sensors with high-temperature operating capabilities, mainly for automotive, gas turbine engine and aerospace applications was investigated from this study as alternative silicon carbide to silicon in the fabrication of these devices.